Zinah Dalam Cerita Pewayangan: Studi Kasus Wisrawa Dan Sukeksi - YB. Rahno Triyogo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
Adultery is often regarded as betrayal because of its disloyalty towards oneself, others, and the Divine. Adultery is a very serious moral crime because it destroys human dignity as the supreme creature of Divine creation. Therefore, anyone who has committed adultery in religious language is called sin. The purpose of this study is to analyze adultery in wayang characters namely Wisrawa and Sukeksi. The meaning approach is used to analyze the problems. The results show that the sin of adultery does not only give a negative impact to the perpetrators but also to their offspring. Adultery is a moral offense and the offender will get moral sanctions from the community (social sanctions) as well as from the Divine. As a result of the parents' actions, their offspring also bear the sanctions. The sanctions referred to in the fictional tradition often appear in physical, mental, or behavioral defects.Keywords: meaning, adultery, wayang stories, Wisrawa, Sukeksi